The Role of Literary Texts in Developing Sociocultural Competence (Eurasian Scientific Herald, 2022)
The article considers about the use of literary texts for the formation of social competence in the process of learning a foreign language in high schools. A modern professional should be prepared to cross-cultural communication, which goes beyond his professional sphere. Nowadays important is the ability and willingness of the university graduate to communicate with native speakers in everyday life, because personal contacts, human relationships often play a decisive role for the achievement of mutual understanding between different cultures.